Effects of COVID-19 on Mental Health and Its Relationship With Death Attitudes and Coping Styles Among Hungarian, Norwegian, and Turkish Psychology Students - Oker, Kemal; Reinhardt, Melinda; Schmelowszky, Ágoston (Frontiers in Psychology, 2022)
The purpose of the current study was to investigate the mental effects of COVID-19 and its relationship with death attitudes and coping styles among Hungarian, Norwegian and Turkish adults. 388 participants from Hungary (N=122; 31.4%), Norway (N=96; 24.7%) and Turkey (N=170; 43.8%) were recruited during the pandemic. The Depression, Anxiety and Stress Scale, the Impact of Event Scale-Revised, the Carver Brief COPE Inventory and the Death Attitude Profile-Revised were used. The results indicated that Escape Acceptance might be the most maladaptive death attitude during COVID-19, as it was related to poorer mental health among the Hungarian, Norwegian and Turkish university students. Self-blame, behavioral-disengagement, self-distraction and substance-use coping styles were also related to poorer mental health, whereas positive-reframing (only among the Hungarian and Turkish participants) and humor (only among the Norwegian participants) were related to better mental health among our sample in the context of COVID-19. The findings implied that death attitudes and coping styles may differ in their efficacy among the Hungarian, Norwegian and Turkish participants. These differences were discussed in detail in the discussion part. During the pandemic, practitioners might pay closer attention to patients with higher Escape Acceptance death attitude and patients who use the dysfunctional coping styles. Additionally, patients can be encouraged to use techniques involving positive-reframing and humor coping styles.